Entwicklung und Evaluation eines Schnellinformationssystems im Speerwurf - Hassan, E.; Schöllhorn, W. I.; Kunthoff, R.; Jaitner, T. (Messplätze, Messplatztraining, motorisches Lernen: ausgewählte Beiträge; 5. gemeinsames Symposium der dvs-Sektionen Biomechanik, Sportmotorik und Trainingswissenschaft; Universität Leipzig, Sportwissenschaftliche Fakultät, 19. bis 21. September 2002 / Veranst.: Sportwissenschaftliche Fakultät der Universität Leipzig ..., 2003)
A mobile measuring and feedback training system for javelin was developed. In order to evaluate the system a training experiment was accomplished in Egypt. 10 sport students trained javelin throwing over 32 training sessions. G1 (n = 5) performed in each training unit 6 additional throws with the feedback training system. Both groups improved their throwing performance after training, whereby the performance of group 1 increased significantly higher. It can be concluded that the training with the feedback training system can provide positive effects. For the evaluation of the diagnosis equipment as quick information system further training experiments are necessary.